Early diagnosis of small airway disease in asymptomatic polishing sector workers of a leather factory - Sruthi Priyadarsini S; Chandrasekar Chokalingam; Balamurugan Shanthalingam; Manikandan Nagesh; Manoj Ramanathan (Asian Journal of Medical Sciences, 2024)
Background: The leather industry stands as one of India’s burgeoning sectors, boasting significant manpower. Workers in the finishing sector, particularly those involved in polishing, face heightened risks due to exposure to formaldehyde, aniline, and resins, which can lead to respiratory complications. Aims and Objectives: The aims and objectives of the study are to determine the small airway obstruction in asymptomatic finishing sector workers of a leather factory. Materials and Methods: The current study was a cross-sectional study conducted in a leather factory located in Chennai, Tamil Nadu. A random sample of 60 workers was drawn from different sectors of a leather factory. Basic demographic details, smoking history, nature of work, exposure to irritants along with duration, and respiratory symptoms were collected. All workers were subjected to spirometry as per ATS guidelines and the results were analyzed. Association between length (years) of exposure, respiratory symptoms, and spirometry impairment among the workers were analysed. Results: Out of 60 samples, 38 were exposed to irritants and 22 were not exposed to irritants. Out of 38, 25 had small airway disease, seven had large airway obstruction, one had a restrictive pattern, and five had normal spirometry. 42.1% of them were asymptomatic. Conclusion: Small airway obstruction is notably prevalent, especially among asymptomatic workers in the polishing sector. Prolonged exposure is associated with the development of large airway obstructive disease. This study underscores the importance of continuous monitoring for airway diseases in occupationally exposed workers, advocating for timely preventive and protective measures to curb disease progression.